Sustaining Management Commitment to Workplace Health Programs:: The Case of Participatory Ergonomics - Dixon, Shane; Theberge, Nancy; Cole, Donald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
This article investigates management commitment to workplace health and safety through an analysis of the implementation of participatory ergonomic (PE) interventions in three worksites. The PE programs were established to address the burden of work-related musculoskeletal disorders. Drawing upon interview and observational data, the analysis examines the evolution of managerial support for PE programs over time and in the context of pressures internal and external to the worksites. Ergonomic Change Teams in all three sites experienced problems establishing authority to act as change agents and in accessing employee time to carry out their activities. Resolution of these problems was heavily contingent on the commitment of senior management, and the efforts of individual management personnel to intervene in support of the PE program. Our findings highlight that “management” is not a monolithic entity and managerial structures are often marked by divisions in priorities, including health and safety.